Correlation among perceived stress, emotional intelligence, and burnout of resident doctors in a medical college of West Bengal: A mediation analysis - Satabdi Mitra; Aditya Prasad Sarkar; Dibakar Haldar; Asit Baren Saren; Sourav Lo; Gautam Narayan Sarkar (Wolters Kluwer Medknow Publications, 2018)
Background: Perceived stress and burnout are by-products of powerless responsibility imposed on resident doctors. Emotional intelligence (EI) works as an adapting and coping tool. Objective: The objective of this study is to find out the role of work-related perceived stress on burnout and influence of EI on it. Methods: A descriptive cross-sectional study was conducted from February to April 2016 among 63 resident doctors of different departments of Bankura Sammilani Medical College and Hospital. Data were collected through a self-administered questionnaire for background characteristics and work-related variables. Cohen perceived stress scale, Trait EI, and Shirom-Melamed burnout questionnaire were applied for measuring perceived stress, EI, and burnout, respectively. Statistical analysis was done with of SPSS version 22.0, and for mediation analysis, Andrew F. Hyne's SPSS macro was adopted. Nonparametric bootstrapping was done assuming small sample. Results: Out of complete responses, 67%, 22.9%, and 9.8% were from clinical, paraclinical, and preclinical specialties, respectively. Burnout had a significant positive correlation with perceived stress and in negative correlation with EI-well-being and positive correlation with EI-self-control and sociability. Physical fatigue factor of burnout had a significant positive correlation with EI-emotionality. Perceived stress had a negative correlation with EI-well-being. On mediation analysis, assuming EI as a mediator, total, direct, and indirect effects of perceived stress on burnout were significant (<0.05). Mediation was proved to act with percent mediation of 0.07. Conclusion: There was definite mitigating effect of EI on burnout by perceived stress among resident doctors. This necessitates more attention by decision-makers toward this burning problem for the sake of care of caregivers.